Islamophobia: Discrimination Against Muslims in America in Attempt to Maintain Global Hegemony - Nisa, Sayyidah Ilman (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Islamophobia emerged in 1992 and has spread since9/11 when a terrorist attack brought down the Twin Towersof the World Trade Center (WTC) in New York. In itshistory, America is the inheritor of the "WesternDomination" of Europe during the imperialism era. Thenwith an increasingly advanced era, globalization isincreasingly demanding to carry out all foreign policies ofa country that does not contain elements of violence andupholds peace. So America uses soft power in issuing all itspolicies, one of which is related to the issue ofIslamophobia. The number of issues of anti-Islamdiscrimination in the west has attracted a lot of internationalattention, so this is the reason why the writer investigatesthis matter. The purpose of this study is to find out theAmerican Strategy on Islamophobia to uphold worldhegemony. By using descriptive qualitative researchanalysis techniques and literature studies such as sourcesfrom books, journals, documents, and reports. The authorfinds that America uses all the power it has to influenceother countries. This finding is corroborated by the conceptof framing in the media to spread Islamophobia. By relyingon its strength, America gets financial assistance fromvarious lines as a supporter of US policy. In addition, theauthor also analyzes the constructivist theory approachwhere all phenomena that occur are based on constructionresults with various national interests and actors behindthem. In the end, it aims to find out the indications andobjectives of the current and future United States foreignpolicy in its international politics as well as efforts tominimize anti-Islamic sentiment in the west.